Estrogen associations with human pregnancy related increases in cytochrome P450 3A activity - Fashe, Muluneh M.; Lee, Jonghwa; Grieco, Joseph T.; Fallon, John K.; Mulrenin, Ian R.; Gower, Megan N.; Jackson, Klarissa D.; Boggess, Kim A.; Lee, Craig R. (Frontiers in Pharmacology, 2025)
IntroductionIncreased CYP3A-mediated drug clearance during pregnancy can lead to subtherapeutic dosing of CYP3A substrates. Pregnancy-related hormones (PRHs) increase CYP3A4 expression and activity in cultured human hepatocytes. However, the factors in maternal circulation that regulate pregnancy-mediated changes in CYP3A activity remain unclear.MethodsThis study investigated the association between maternal plasma concentrations of key steroidal PRHs and biomarkers of CYP3A activity in human pregnancy, and the impact of individual PRHs on CYP3A4 expression in primary human hepatocytes. Concentrations of estrone (E1), estradiol (E2), progesterone (P4), and cortisol (CRT), and 4β-hydroxycholesterol (4β-OH-CHO) and the 4β-OH-CHO:CHO ratio (endogenous biomarkers of CYP3A activity), were quantified in human plasma across a spectrum of pregnancy states: healthy nonpregnant controls (n = 4), healthy pregnant volunteers (n = 6), and pregnant patients diagnosed with preeclampsia (n = 8).ResultsPlasma 4β-OH-CHO concentrations (median [25%–75%]) were higher in healthy pregnant (141 [115, 165] ng/mL) and preeclampsia patients (129 [90.5, 191] ng/mL) compared to nonpregnant controls (69.8 [45.8, 82.5] ng/mL). In healthy pregnant and preeclampsia patients, plasma E1 (r = 0.687, p = 0.007) and E2 (r = 0.551, p = 0.041) concentrations positively correlated with plasma 4β-OH-CHO concentrations. Conversely, no association between P4 (r = 0.068, p = 0.817) or CRT (r = -0.115, p = 0.696) concentrations and 4β-OH-CHO were observed. Cultured human female primary hepatocytes were exogenously exposed in vitro to PRHs and absolute CYP protein concentrations were quantified. Consistent with the human plasma sample associations, E1 and E2 induced CYP3A4 mRNA and total CYP3A protein concentrations in a concentration-dependent manner.DiscussionAltogether, these data suggest that increased concentrations of E1 and E2 contribute, at least in part, to increased hepatic CYP3A expression and activity during pregnancy in humans.